Assessment of chemical compositions in coral skeletons (Acropora digitifera and Porites australiensis) as temperature proxies - Sakata, Shoko; Inoue, Mayuri; Tanaka, Yasuaki; Nakamura, Takashi; Sakai, Kazuhiko; Ikehara, Minoru; Suzuki, Atsushi (Frontiers in Marine Science, 2024)
Although biogenic carbonates, such as foraminifera and coccolithophorids, are valuable tools for reconstructing past environments, scleractinian corals also offer environmental data from tropical to subtropical regions with a higher time resolution. For example, oxygen isotopes (δ18O) and strontium-calcium (Sr/Ca) ratios have been utilized to reconstruct sea surface temperatures and salinity, primarily through the use of massive-type Porites sp. from the Pacific, as well as corals like Diploria and Montastrea from the Atlantic. While a few types of corals other than Porites have been utilized in paleoclimate studies, comprehensive evaluations of their geochemical tracers as temperature proxies have not been thoroughly conducted. Therefore, in this study, we focused on branching-type Acropora, which are found worldwide and are often present in fossil corals. We conducted a comparison of the chemical compositions (δ18O, δ13C, Sr/Ca, U/Ca, Mg/Ca, and Ba/Ca) of Acropora digitifera and Porites australiensis through temperature-controlled culture experiments. The validity of using the chemical components of A. digitifera as temperature proxies was then evaluated. Three colonies of A. digitifera and P. australiensis were collected for culture experiments on Sesoko Island, Okinawa, Japan. We reared coral samples in seawater with five different temperature settings (18, 21, 24, 27, 30°). The calcification rate and photosynthesis efficiency (Fv/Fm) of each nubbin were measured during the experimental period. After the culture experiment for 77 days, chemical components in skeletal parts grown during the experiment were then measured. Consequently, the mean growth rates and Fv/Fm throughout the experiment were higher for A. digitifera (0.22%/d and 0.63 for growth rate and Fv/Fm) compared to those for P. australiensis (0.11%/d and 0.38 for growth rate and Fv/Fm). This suggests that the higher efficiency of photosynthesis in A. digitifera would promote greater calcification compared to P. australiensis. Regarding the potential use as temperature proxies, A. digitifera exhibited a strong negative correlation, on average, between δ18O and the water temperature (r = 0.95, p< 0.001). The temperature dependency was found to be comparable to that reported in Porites corals (-0.11 and -0.17 ‰/°C for P. australiensis and A. digitifera, respectively). Thus, the δ18O of A. digitifera appeared to be a useful temperature proxy, although it was also slightly influenced by skeletal growth rate at the same temperature. A strong negative correlation was also observed between the mean Sr/Ca ratio and temperature in A. digitifera (r = 0.61, p< 0.001) as well as P. australiensis (r = 0.56, p< 0.001), without a clear influence from the skeletal growth rate. Therefore, the skeletal Sr/Ca ratio in corals may have been primarily influenced by water temperature, although large deviations in Sr/Ca were observed in A. digitifera, even at the same temperature settings. This deviation can be reduced by subsampling an apical part of a polyp including the axis of skeletal growth. The U/Ca ratio of A. digitifera appeared to be affected by internal pH variation within the corals, especially at 30°C. Similar to U/Ca ratios, metabolic and kinetic effects on corals were observed in δ13C of A. digitifera at 18 and 30°C. In addition, considering the variation pattern of both U/Ca and δ13C of A. digitifera at 30°C, it has been suggested that respirations may overwhelm photosynthesis for coral samples at 30°C. Therefore, the U/Ca and δ13C of A. digitifera could potentially be used as proxies of biomineralization processes, whereas the δ18O and Sr/Ca displayed a high possibility of acting as temperature proxies.